Renewable Energy: A Cornerstone in The Transition Toward a Sustainable Future - Jahada Haluti, Islamiyati; Muliadi; Sri Indah Setiyaningsih MSM; Baihaqi; Adean Mayasri (Bansigom Na Publisher, 2024)
The transition toward a sustainable future is increasingly dependent on the integration of renewable energy sources. This article explores the pivotal role that renewable energy plays in achieving sustainability goals. It discusses various forms of renewable energy, including solar, wind, hydro, and geothermal power, and examines their potential to reduce carbon emissions and mitigate climate change. Additionally, the article addresses the economic and social benefits of renewable energy, such as job creation, energy security, and reduced reliance on fossil fuels. The challenges and barriers to widespread adoption are also considered, alongside potential solutions and policy recommendations. Ultimately, this article underscores the necessity of renewable energy as a cornerstone in building a sustainable and resilient future for all.